Relationships Between Resilience, Mental Well-Being, and COVID-19 Worries in Collegiate Student-Athletes - Watts, Cade J.; Hilliard, Robert C.; Graupensperger, Scott (Frontiers in Sports and Active Living, 2022)
The onset of the COVID-19 pandemic was associated with robust declines in well-being for collegiate student-athletes. Worries about COVID-19 have frequently been associated with worsening well-being; therefore, it is important to examine protective factors against well-being decrements. Resilience, one’s ability to respond to stress and adversity, may be one such factor. Despite this possible influence, resilience has not yet been studied in student-athletes in this context as the pandemic has progressed. Therefore, the purpose of this study was to examine the moderating role of resilience on the relationship between COVID-19 worries and well-being. In this cross-sectional design, National Collegiate Athletic Association Division III athletes (N = 91) at one university completed surveys on COVID-19 worries, resilience, and well-being between February and March 2021. All competitions had been postponed until the Spring 2021 semester. The findings revealed a negative correlation between COVID-19 worries and well-being (r = -.21, p = .05) and a positive correlation between resilience and well-being (r = .44, p < .001). Additionally, multiple regression and simple slopes analyses showed that individuals with higher resilience endorsed greater scores of well-being, even when COVID-19 worries increased (β = 0.38, p = .02). In conclusion, our results suggest that resilience had a moderating effect on the relationship between COVID-19 worries and well-being.